ALUR PROGRAM PENDIDIKAN KARAKTER SELF AWARENESS DAN SELF RESPECT BERBASIS KONSERVASI: PROGRAM WALI POHON, WALI FAUNA DAN WALI MANGROVE: CONSERVATION-BASED SELF AWARENESS AND SELF RESPECT CHARACTER EDUCATION PROGRAM FLOW: TREE GUARDIAN, FAUNA GUARDIAN AND MANGROVE GUARDIAN PROGRAM - Handayani, Sri; Sulastini, Rita (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
Strong character is formed through education, which plays an important role in individual and societal success. Environmental education and sustainable conservation can improve future prosperity, but still face constraints on practical methods and skills in Indonesia. Environmental awareness needs to be instilled for humans to be part of it, with conservation programs involving all sectors, not just education. Wanadri has launched a conservation-based mentorship program for all age groups, especially the younger generation. This research uses a natural ethnographic approach to examine the development of participants' self-awareness and responsibility. It is hoped that this program will not only provide environmental knowledge but also form a socially responsible and sustainable character. Improving the quality of environmental education is necessary to maintain Indonesia's biodiversity and natural resources, with the active involvement of all stakeholders.